Aluminium acetate as alternative cross-linker for temperature controlled gel-casting and joining of ceramics. Issue 5 (April 2016) - Brandes, Christoph; Hoog Antink, Marieke; Kroll, Stephen; Treccani, Laura; Rezwan, Kurosch
Abstract: In an earlier established gel-casting process, the biopolymer alginate is cross-linked with Ca 2+ -ions released through the temperature controlled dissolution of calcium iodate-particles (Ca(IO3 )2 ). In this study, aluminum acetate (AlAc) is compared to Ca(IO3 )2 as an alternative temperature controlled cross-linker for an alginate–alumina slurry. Both cross-linkers are characterized regarding gel-forming properties, resulting microstructure, impurities, mechanics of sintered parts and the ability of joining ceramic blocks in the green state via connecting gelation with and without adding slurry. Rheological measurements show that both cross-linker have a similar gelling behavior and lead to gelled blocks of high quality. AlAc-particle create a denser and more homogenous microstructure, while Ca(IO3 )2 -particles induce pores, abnormal grain growth and lower mechanical values. Nevertheless Ca(IO3 )2 shows excellent joining properties which makes it a suitable alternative to pressure joining. In summary, AlAc is an excellent alternative cross-linker but Ca(IO3 )2 remains the method of choice for joining gelled bodies.